Type the correct answer in the box. Use numerals instead of words. If necessary, use / for the fraction bar.

Evaluate.
-2(x + 6) + 3 = -11x + 4(x + 4)

1 answer

Let's solve the equation step by step:

Start with the original equation: \[ -2(x + 6) + 3 = -11x + 4(x + 4) \]

Distribute on both sides: \[ -2x - 12 + 3 = -11x + 4x + 16 \]

Combine like terms: \[ -2x - 9 = -11x + 4x + 16 \] \[ -2x - 9 = -7x + 16 \]

Now, add \(7x\) to both sides: \[ -2x + 7x - 9 = 16 \] \[ 5x - 9 = 16 \]

Next, add \(9\) to both sides: \[ 5x = 16 + 9 \] \[ 5x = 25 \]

Now, divide by \(5\) to solve for \(x\): \[ x = \frac{25}{5} \] \[ x = 5 \]

The final answer is: \[ 5 \]